Transition Matrix Instability and Credit Risk - Basson, Lodewikus Jacobus; van Vuuren, Gary (International Journal of Economics and Financial Issues, 2026)
Credit risk stress testing has emerged as an essential risk management tool employed by both by financial institutions and regulatory authorities. Its implementation involves substantial complexity stemming from the requirement to forecast complete portfolio creditworthiness changes under specified macroeconomic scenarios across multi-year horizons. This complexity arises from the integration of numerous model parameters governing changes over time. With the standard practice involving the specification of baseline parameters calibrated to average economic conditions that are subsequently transformed to stressed states through macroeconomic models. A critical – but often overlooked – consequence of this parameterisation and calibration approach is that it implicitly defines a unique equilibrium portfolio that exists independently of the financial institution's actual portfolio composition which emerges purely from the interaction of model parameters rather than from existing exposure characteristics. The mathematical structure of these models creates an inherent tendency for current portfolios to converge toward this parameter-implied portfolio over the projection horizon. When stress test parameters are inconsistent with actual portfolio characteristics the convergence process generates spurious effects in projected portfolio default rates (a common situation arising when banks utilise external data sources or industry benchmarks due to insufficient internal historical data). The projected portfolio defaults can originate from the parameterisation itself rather than from the economic stress being modelled. This effect can potentially produce misleading risk assessments that compromise both internal capital allocation decisions and regulatory capital requirements.